Clopidogrel Increases Dasabuvir Exposure With or Without Ritonavir, and Ritonavir Inhibits the Bioactivation of Clopidogrel - Itkonen, Matti K.; Tornio, Aleksi; Lapatto‐Reiniluoto, Outi; Neuvonen, Mikko; Neuvonen, Pertti J.; Niemi, Mikko; Backman, Janne T. (Clinical pharmacology and therapeutics, 2019)
Dasabuvir is mainly metabolized by cytochrome P450 (CYP) 2C8 and is predominantly used in a regimen containing ritonavir. Ritonavir and clopidogrel are inhibitors of CYP3A4 and CYP2C8, respectively. In a randomized, crossover study in 12 healthy subjects, we examined the impact of clinical doses of ritonavir (for 5 days), clopidogrel (for 3 days), and their combination on dasabuvir pharmacokinetics, and the effect of ritonavir on clopidogrel. Clopidogrel, but not ritonavir, increased the geometric mean AUC0‐∞ of dasabuvir 4.7‐fold; range 2.0–10.1‐fold (P = 8·10−7), compared with placebo. Clopidogrel and ritonavir combination increased dasabuvir AUC0‐∞ 3.9‐fold; range 2.1–7.9‐fold (P = 2·10−6), compared with ritonavir alone. Ritonavir decreased the AUC0‐4h of clopidogrel active metabolite by 51% (P = 0.0001), and average platelet inhibition from 51% without ritonavir to 31% with ritonavir (P = 0.0007). In conclusion, clopidogrel markedly elevates dasabuvir concentrations, and patients receiving ritonavir are at risk for diminished clopidogrel response.